2016
DOI: 10.1590/s1984-29612016083
|View full text |Cite
|
Sign up to set email alerts
|

Ticks parasitizing bats (Mammalia: Chiroptera) in the Caatinga Biome, Brazil

Abstract: In this paper, the authors report ticks parasitizing bats from the Serra das Almas Natural Reserve (RPPN) located in the municipality of Crateús, state of Ceará, in the semiarid Caatinga biome of northeastern Brazil. The study was carried out during nine nights in the dry season (July 2012) and 10 nights in the rainy season (February 2013). Only bats of the Phyllostomidae and Mormoopidae families were parasitized by ticks. The species Artibeus planirostris and Carolia perspicillata were the most parasitized. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…While neither live virus nor nucleic acid of CCHFV has been detected from bats, serologic evidence suggests past infection of populations of bats across a diverse geographic range [15,16,17]. Further, bats are often parasitized by both soft and hard ticks, which occupy a diverse range of ecological niches in endemic countries [18,19,20]. A 2016 seroprevalance study by Müller and colleagues examining 16 African bat species ( n = 1,135) found that the prevalence of antibodies against CCHFV was much higher in cave-dwelling bats (3.6%–42.9%, depending on species) than foliage-living bats (0.6%–7.1%) [15].…”
Section: Members Of the Order Bunyaviralesmentioning
confidence: 99%
See 1 more Smart Citation
“…While neither live virus nor nucleic acid of CCHFV has been detected from bats, serologic evidence suggests past infection of populations of bats across a diverse geographic range [15,16,17]. Further, bats are often parasitized by both soft and hard ticks, which occupy a diverse range of ecological niches in endemic countries [18,19,20]. A 2016 seroprevalance study by Müller and colleagues examining 16 African bat species ( n = 1,135) found that the prevalence of antibodies against CCHFV was much higher in cave-dwelling bats (3.6%–42.9%, depending on species) than foliage-living bats (0.6%–7.1%) [15].…”
Section: Members Of the Order Bunyaviralesmentioning
confidence: 99%
“…A number of hematophagous arthropods feed on bats, including bat flies (genera Nycteribiidae and Streblidae ), bat bugs and bed bugs (family Cimicidae ), and ticks (families Argasidae and Ixodidae ) [18,20,21,167,168,169,170,171,172]. Viruses of medical and veterinary significance have also been isolated from these arthropods [21,173,174,175].…”
Section: Relationships Between Bats and Arthropodsmentioning
confidence: 99%
“…Nowadays, we know that O. hasei is a wide spread species in Brazil and that three-roosting bats Artibeus planirostris and Noctilio spp. could act as main hosts [87,[130][131][132]. With the exception of recent collection of larvae on A. planirostris [87], knowledge on the distribution of O. hasei along the Brazilian Amazon is still poorly vague.…”
Section: Soft Ticks In the Brazilian Amazonmentioning
confidence: 99%
“…El bioma Caatinga se refiere a los ecosistemas semiáridos del noreste de Brasil, con baja precipitación y humedad (15). En este bioma, los registros de garrapatas y sus agentes microbianos son más frecuentes en animales silvestres y domésticos, siendo escasos los asociados con humanos (11,16,17,18,19). Curiosamente, dentro del bioma Caatinga, existen áreas aisladas de bosque que se asemejan a la selva humeda tropical atlántica a mayor altitud, generalmente >400 metros sobre el nivel del mar.…”
Section: Introductionunclassified